Unwillingness to prescribe PrEP by health care professionals of specialized HIV/AIDS services in Northeastern Brazil - Juliana de Souza Lamônica; Laio Magno; Julia Elen Jesus da Silva Santos; Ines Dourado; Adriano Maia dos Santos; Marcos Pereira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
This study aimed to analyze factors associated with the unwillingness to prescribe pre-exposure prophylaxis (PrEP) by health care professionals of specialized HIV/AIDS services. This is a cross-sectional study with 252 health care professionals in 29 specialized care services (SCSs) in HIV/AIDS in 21 municipalities in the state of Bahia, Brazil. The inclusion criterion was that the professional had worked for at least six months in the service. Sociodemographic, occupational, and behavioral data were collected using a questionnaire. Logistic regression was performed with an estimation of crude and adjusted odds ratio (OR) and respective 95% confidence intervals (95%CI). The unwillingness to prescribe PrEP was 15.2% (95%CI: 10.8-19.6). The factors associated with unwillingness to prescribe PrEP were non-prescription of HIV self-tests for key populations (adjustedOR = 5.4; 95%CI: 1.3-22.4) nor post-exposure prophylaxis (adjustedOR = 2.00; 95%CI: 1.3-3.1), location of the SCS in the state capital (adjustedOR = 3.9; 95%CI: 1.4-10.2), and SCSs without PrEP offer (adjustedOR = 1.7; 95%CI: 1.1-2.8); professionals who have not reported the need to conduct training and courses (adjustedOR = 1.3; 95%CI: 1.1-1.8), or training with more experienced professionals (adjustedOR = 1.8; 95%CI: 1.1-3.8), was associated with a lower proportion of unwillingness to prescribe PrEP. Our results indicate that health care professionals' contextual, organizational, and training factors can contribute to PrEP indication. We suggest expanding ongoing training in combined HIV prevention among health care professionals and increasing the availability of PrEP in health services.